Integrating nutrition science and consumer behaviour into future food policy. (8th July 2019) - Woodside, Jayne V; Klassen Wigger, Petra; Legrand, Philippe; Mensink, Ronald P; Mozaffarian, Dariush; Sievenpiper, John
Abstract: The session 'Advancing risk assessment science – Nutrition' at EFSA's third Scientific Conference 'Science, Food and Society' aimed to foster the ongoing debate on the extent to which single nutrients, whole foods and overall diets may impact human health in wealthy populations, and to explore how societal and technological developments could affect food choices and diets in the future. The overarching goal of the session was to discuss how dietary guidelines could evolve to account for the switch from single nutrient deficiencies to diseases of malnutrition in all its forms as the predominant public health concern in developed countries. Speakers addressed the contribution of single nutrients to the prevalence of chronic metabolic diseases, discussed the need to move towards diets focusing on whole foods and overall eating patterns, provided insides on food innovation and consumer behaviour and stressed the need for multidisciplinary approaches to face these challenges.